Hypoxia-mediated epicardial signaling coordinates coronary angiogenesis and myocardial expansion during zebrafish ventricle maturation - Ku-Chi Tsao; Isaac Bakis; Shuofei Sun; Maki Nakayama; Zachary Kalmanson; Laila Abd Elmagid; Joshua S. Shuster; Yu Xia; James V. Eichenbaum; Fang Zhou Yu; Megan L. McCain; Todd Evans; et al. (Proceedings of the National Academy of Sciences, 2026)
During cardiac development, the myocardium expands in response to physiological demands to achieve proper cardiac morphology and functional contractility, while simultaneously integrating with the developing coronary vasculature. However, the mechanisms governing this ordered expansion remain poorly understood. Here, we found that regional hypoxia drives local tissue thickening, which in turn exacerbates a hypoxic microenvironment. We demonstrate that epicardial hypoxia serves as a central regulatory mechanism, coordinating both coronary angiogenesis and myocardial expansion during juvenile zebrafish heart development. This mechanism activates discrete spatial patterns of epicardial gene expression, including vegfaa , loxl2a , and col12a1b . Through live and fixed imaging, we find that cardiomyocytes and endothelial cells exhibit coordinated expansion patterns through third-party epicardial signals that are required for both coronary development and myocardial expansion. Using cxcr4a um20 mutants lacking functional coronary vessels, we show that coronary vessels provide negative feedback on epicardial hypoxia, while positively responding to the same hypoxic cues that drive myocardial expansion. Disruption of this negative feedback leads to increased myocardial stiffness through dysregulated extracellular matrix crosslinking as observed in pathological conditions such as cardiomyopathies. These findings establish the role of regional epicardial hypoxia within a fundamental regulatory network that drives appropriate regional tissue growth with integrated vascular supply during cardiac morphogenesis.